Non-invasive evaluation of lower urinary tract symptoms (LUTS) in men - Reshma Mangat; Henry S.S. Ho; Tricia L.C. Kuo (Asian Journal of Urology)
Lower urinary tract symptoms (LUTS) are common in males over the age of 40 years old and are likely to increase with an aging population. Currently urodynamic studies are the gold standard to determine the aetiology of voiding dysfunction and LUTS. However, due to its invasive nature, a great number of non-invasive ultrasound based investigations have been developed to assess patients with symptomatic LUTS. The clinical application of non-invasive tests could potentially stratify patients who would require more invasive investigations and allow more precise patient directed treatment. A PubMed literature review was performed and we will discuss the non-invasive investigations that have been developed thus far, focusing on bladder wall and detrusor wall thickness (BWT & DWT), ultrasound estimated bladder weight (UEBW) and intravesical prostatic protrusion (IPP).